Reforming Nitrate Metabolism for Enhancing L-Arginine Production in Corynebacterium crenatum Under Oxygen Limitation - Huang, Mingzhu; Zhu, Lingfeng; Feng, Lin; Zhan, Li; Zhao, Yue; Chen, Xuelan (Frontiers in Microbiology, 2022)
Various amino acids are widely manufactured using engineered bacteria. It is crucial to keep the dissolved oxygen at a certain level during fermentation, but accompanied by many disadvantages, such as high energy consumption, reactive oxygen species, and risk of phage infections. Thus, anaerobic production of amino acids is worth attempting. Nitrate respiration systems use nitrate as an electron acceptor under anoxic conditions, which is different from the metabolism of fermentation and can produce energy efficiently. Herein, we engineered Corynebacterium crenatum to enhance L-arginine production under anaerobic conditions through strengthening nitrate respiration and reforming nitrogen ﬂux. The construction of mutant strain produced up to 3.84 g/L L-arginine under under oxygen limitation with nitrate, and this value was 131.33% higher than that produced by the control strain under limited concentrations of oxygen without nitrate. Results could provide fundamental information for improving L-arginine production by metabolic engineering of C. crenatum under oxygen limitation.